The 5 personality patterns : your guide to understanding yourself and others and developing emotional maturity - Kessler, Steven (Australia : Bodhi Tree Press, 2015)
This bestselling book marks a major advance in the psychology of personality. Suddenly, you can see what's going on inside people: you can see what motivates and matters to them and how to influence and communicate with them successfully. Finally, you have a simple, clear, true-to-life map of personality that gives you the key to understanding people and interacting with them successfully. The 5 Personality Patterns is a book that can change your life. "This is one of the most useful popular psychology books I have ever seen. . . . It should become a classic."--- Stephen M. Johnson, author of Character Styles and Characterological TransformationMuch of our human suffering is not necessary. It is created by old safety strategies that helped us survive our childhood traumas, but then got stuck in our bodies. Reinforced by the power of habit, they continue to shape our actions and personality even today. They have become an invisible prison. We live our lives trapped in that prison, repeating the same mistakes over and over again.As we attempt to understand the psychology of success and become successful ourselves, studying the habits of successful people is not enough. To create real self transformation, we must dissolve the obstacles to success buried within us. To reclaim our power and regain control of our lives, we must uncover the old safety strategies and patterns that still run our lives so that we can heal and transform them.Often, these patterns have shaped us so deeply that we think that's who we are. But in fact, they cover up our true self and prevent it from shining out into the world. Finally, we have a map of these patterns, a map that will help you:- Discover how you got stuck and how to get free- Heal your core wounds- Learn the skills you missed- Communicate effectively with others- Develop emotional maturityMany readers seeking self improvement have discovered that this map of personality is even more helpful to them than the Enneagram and Myers-Briggs personality types, because those maps focus on the surface of the body, on your behaviors, while this map starts with the core of the body and how the flow of your life energy got distorted. And that distortion of the flow of life energy through the body is at the root of much of the suffering and conflict we experience in interpersonal relationships. Understanding those differences will dramatically increase your empathy, compassion, and people skills. Understanding how to bridge those differences will dramatically increase your interpersonal communication skills.
Our Eyes Deceive Us -- About Survival Patterns -- The Developmental Stages that Underlie the Survival Patterns -- A Brief Overview of the Survival Patterns -- The Basic Skills Needed for Inner Work -- A Chart of the Survival Patterns -- The Leaving Pattern -- The Merging Pattern -- The Enduring Pattern -- The Aggressive Pattern -- The Rigid Pattern -- Primary and Secondary Patterns -- Getting Yourself Out of Pattern -- Conclusion.
Includes index.
Keywords: PERSONALITY